AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN JERUK PURUT (Citrus hystrix) TERHADAP BAKTERI Salmonella typhi - Yoga Alim Prisnanda; Destik Wulandari (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2022)
The lime leaves (Citrus hystrix) containing alkaloids, flavonoids, saponins and tannins which have antibacterial activity. The aims of the research was to determine the antibacterial effect of lime leaf extract to against Salmonella typhi bacteria. This research was initiated with extracting lime leaves, testing the chemical content of lime leaf extract, identifying bacteria, and testing the antibacterial activity of lime leaf extract using the disc diffusion method. The concentration of extract to used antibacterial activity test with diffusion methode was 2.5%; 5%; 10%. Positive control was chloramphenicol and negative control was DMSO 8%. based on kaffir lime leaf extract test, positively contained flavonoids, alkaloid tannins and saponins. Kaffir lime leaf extract has antibacterial activity for Salmonella thypi bacteria. The antibacterial activity test showed an average inhibition zone of 8 mm at a concentration of 2.5%, 9.6 mm at a concentration of 5% and 11.6 mm at a concentration of 10%.